Seismic fragility curves for integral concrete bridge in Bulgaria - Iliev, Alexander; Stefanov, Dimitar (Građevinski materijali i konstrukcije, 2025)
The determination of seismic behavior is a major issue concerning civil engineers nowadays. The development of computer systems has led to an increasing use of various analytical approaches for determining the seismic response of buildings and structures. This study employs the Capacitive Spectrum Method (CSM) as an indirect approach to calculate fragility curves. In it, the capacity of the structure is represented by the so-called capacity curve which shows the relationship between force and displacement and thus represents the expected response for a given seismic load.In this procedure, the seismic excitation is represented by the 5% elastic response spectrum for the respective location and return period of the seismic input. The Capacitive Spectrum Method (CSM) is based on a direct graphical comparison of the structural capacity (capacitive curve) with the required reduced elastic demand spectrum. In the current paper, the seismic capacity and fragility curves for the integral bridge case study were developed. The so-called fragility models and the relative probabilities of reaching four levels of damage are defined. These curves are used to develop loss models of the built environment. The discrete damage probabilities can be used as input data for determining and estimating various losses and damages in structures.